Early identification of the efficacy of 0.125% atropine treatment for children with Myopia: A prospective pilot study - Zi-Rong Chen; Tsung-Yao Wan; Lan-Hsin Chuang; Chi-Chun Lai; Yih-Shiou Hwang; Yu-Kai Kuo; Ho-Min Chen; Po-Chun Chang; Hung-Chi Chen; Chun-Fu Liu (PLoS ONE, 2025)
Purpose This study aimed to investigate whether early axial length (AL) changes in the short term after 0.125% atropine treatment could predict long-term axial elongation in children with myopia. Methods This was a prospective cohort study involving children aged 5–15 years with myopia who were treated with 0.125% atropine for myopia control. AL was measured 1–2 months after starting treatment and then every 3 months for follow-up visits. Regression analysis was used to develop a model of AL changes with time. A generalized estimating equation (GEE) model was then used to identify correlations between the early AL changes and long-term AL changes. Results Eighty eyes of 40 patients (mean age 8.4 years) were included in the final analysis. The estimation curve of AL changes with time indicated that the AL decreased at 67 days (the turning point in the regression model) after 0.125% atropine treatment and then increased gradually with time. Univariate GEE showed that a larger AL elongation in the initial 4 months was significantly associated with AL changes at 6 months (β = 0.354, P = 0.020, 6 ~ 12 months period from baseline) and 12 months (β = 0.560, P = 0.045, 6 ~ 18 months period from baseline) after that period in all myopic eyes. Conclusions The magnitude of AL elongation in the initial 4 months of 0.125% atropine treatment correlated positively with the further half-year and one-year AL changes. Identifying these changes may be useful for controlling refractory myopia in children.